2000
DOI: 10.1242/jcs.113.17.3093
|View full text |Cite
|
Sign up to set email alerts
|

The protease-activated receptor-2 upregulates keratinocyte phagocytosis

Abstract: The protease-activated receptor-2 (PAR-2) belongs to the family of seven transmembrane domain receptors, which are activated by the specific enzymatic cleavage of their extracellular amino termini. Synthetic peptides corresponding to the tethered ligand domain (SLIGRL in mouse, SLIGKV in human) can activate PAR-2 without the need for receptor cleavage. PAR-2 activation is involved in cell growth, differentiation and inflammatory processes, and was shown to affect melanin and melanosome ingestion by human kerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…The protease‐activated receptor‐2 (PAR‐2) is one of the few molecular players described to control melanin transfer both in vivo and in vitro. Moreover, it is known that PAR‐2 stimulation leads to the enhancement of melanin transfer, as well as keratinocyte phagocytosis 13–17 . In addition, we showed that PAR‐2 regulates the uptake of melanocores, but not melanosomes 18 .…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…The protease‐activated receptor‐2 (PAR‐2) is one of the few molecular players described to control melanin transfer both in vivo and in vitro. Moreover, it is known that PAR‐2 stimulation leads to the enhancement of melanin transfer, as well as keratinocyte phagocytosis 13–17 . In addition, we showed that PAR‐2 regulates the uptake of melanocores, but not melanosomes 18 .…”
Section: Introductionmentioning
confidence: 64%
“…Moreover, it is known that PAR-2 stimulation leads to the enhancement of melanin transfer, as well as keratinocyte phagocytosis. [13][14][15][16][17] In addition, we showed that PAR-2 regulates the uptake of melanocores, but not melanosomes. 18 Nonetheless, it is not clear what is the route followed by melanin to enter keratinocytes.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…[2][3][4][5][6] Keratinocytes ingest the synthesized melanin through the melanocyte dendrite, following an increase of protease-activated receptor 2 (PAR-2) activation. [7][8][9][10][11] Trypsin and mast cell tryptase are known to be activators of PAR-2. 12, 13 Accordingly, the inhibitors of these enzymes (tyrosinase, trypsin, and tryptase) have the potential to become hypopigment agents, which prevent the overproduction of melanin in the skin.…”
Section: ' Introductionmentioning
confidence: 99%
“…Dendritic cells known as melanocytes, which are located at basal lamina, are responsible for producing melanin in the skin . Tyrosinase (EC 1.14.18.1) synthesized in the melanocytes plays an important role in melanin synthesis, such as the hydroxylation of l -tyrosine to 3,4-dihydroxy- l -phenylalanine ( l -DOPA), oxidation of l -DOPA to dopaquinone, and oxidation of 5,6-dihydroxyindole to indolequinone. Keratinocytes ingest the synthesized melanin through the melanocyte dendrite, following an increase of protease-activated receptor 2 (PAR-2) activation. Trypsin and mast cell tryptase are known to be activators of PAR-2. , Accordingly, the inhibitors of these enzymes (tyrosinase, trypsin, and tryptase) have the potential to become hypopigment agents, which prevent the overproduction of melanin in the skin. …”
Section: Introductionmentioning
confidence: 99%